Futures research and environmental sustainability theory and method - Lein, James K. (Taylor & Francis Group, 2017)
This book explores the challenges of presenting sustainability as a more actionable or practical concept and identifying approaches that might offer useful assistance in addressing the temporal and spatial representation of sustainability. The underlying premise of this book is that sustainability is a state realized in the future. In that future there is a geographic arrangement of society and economy that agrees with its environmental setting. This future perspective introduces a little examined subject area that can lend significant content to the sustainability challenge: Futures Research.